Afectividad en las familias desligadas - Villarroel Carrión, Mauricio Fabián (2015)
The objective of this research is to determine the type of affective communication in families are alien, relying on the theories applied to the research support as essential to check that, within the family ties does not express the emotional part, nor the establishment of clearcut way of the rules, and rules that must be performed every member of the family environment as benefits to obtain an emotional environment and communicative favorably in the family. In the same way it was demonstrated that the lack of dedication, lack of mutual support, family conflicts and lack of compression, associated with the deficit of the family activities leads them to generate an emotional distance in each of the subjects that make up the family unit, inducing to develop a deterioration of his personality and the subjective part in regard to the perception of family, in this way causes a low self-esteem due to the lack of affection and communication that do not exist in this type of family. In this way was related affective communication from the humanistic approach. Using this approach is directed toward the implementation of the person reaching the realisation, raised on the basis of their own motivations, serving as a benefit to improve the relations between the members of the family life that are managed independently. This study is the product of a mode of qualitative research, descriptive type using the biographical method and analytical, lenders in psychological techniques such as interview, reagents and psychological observation forms. The discussion of the results are based on the psychological techniques applied, concluding that the affective communication is of vital importance for a better family environment, and the constancy of the communication in families are alien becomes an essential tool for improving relations.